Now is the Time for a Postracial Medicine: Biomedical Research, the National Institutes of Health, and the Perpetuation of Scientific Racism. - Perez-Rodriguez, Javier; de la Fuente, Alejandro (American Journal of Bioethics, 2017)
The consideration of racial differences in the biology of disease and treatment options is a hallmark of modern medicine. However, this time-honored medical tradition has no scientific basis, and the premise itself, that is, the existence of biological differences between the commonly known races, is false inasmuch as races are only sociocultural constructions. It is time to rid medical research of the highly damaging exercise of searching for supposed racial differences in the biological manifestations of disease. The practice not only condoned but required by the National Institutes of Health (NIH) of utilizing racial identification as a demographic characteristic with assumed biological implications is at best badly flawed, and at worst unintentionally contributes to perpetuating the fallacy of natural differences between persons of different skin color, which has been used in the past to advance the cause of racial discrimination.